Reproductive and immune effects of chronic corticosterone treatment in male White's treefrogs, Litoria caerulea. (25th May 2015) - Kaiser, Kristine; Devito, Julia; Jones, Caitlin G.; Marentes, Adam; Perez, Rachel; Umeh, Lisa; Weickum, Regina M.; McGovern, Kathryn E.; Wilson, Emma H.; Saltzman, Wendy
Abstract : Long-term elevation of glucocorticoid hormones associated with chronic stress may be detrimental. Chronic treatment of White's treefrogs with exogenous corticosterone reduced eosinophil numbers but did not alter sperm count or sperm viability. We suggest that corticosterone inhibits immune but not reproductive function in this species in response to chronic stress. Abstract : Amphibian populations are declining globally. The potential contribution of glucocorticoid hormones to these declines has received little attention, but chronic elevation of glucocorticoids has been linked to a suite of negative outcomes across vertebrate taxa. Recently, chronic environmental stress has been associated with precipitous declines in sperm count and sperm viability in White's treefrogs ( Litoria caerulea ), but the mechanism remains unknown. In order to determine whether corticosterone is responsible for suppressing reproductive and immune function in this species, we elevated circulating concentrations of corticosterone in 10 male captive-bred frogs via transdermal application for 7 days. We compared sperm count, sperm viability, splenic cell count and circulating leucocyte counts in corticosterone-treated frogs with those in untreated control frogs. Chronic application of exogenous corticosterone led to supraphysiological circulating concentrations of corticosterone, but had no effect on sperm count or viability. However, corticosterone-treated frogs demonstrated a significant decrease in circulating eosinophils, which are immune cells implicated in fighting a variety of pathogens, including extracellular parasites. These findings suggest that although chronic elevation of circulating corticosterone is not necessarily associated with reproductive suppression in this species, it may cause immunosuppression. Thus, chronic glucocorticoid elevations in amphibians might enhance susceptibility to infection with pathogens and parasites, and their potential contributions to global population declines warrant further study.